ANALISIS PENGARUH KAPABILITAS USAHA DAN DIGITAL MARKETING TERHADAP SUSTAINABILITY UMKM KAIN SONGKET DI KABUPATEN SAMBAS DAN KERAJINAN BIDAI DI KABUPATEN BENGKAYANG SEBAGAI WILAYAH PERBATASAN - Hardiansyah, Gusti; Triana M, Neni; Kalis, Maria Christiana; Mahdi, Irfan; Aripin; Yani, Adi (FEB Universitas Sam Ratulangi Manado, 2023)
Abstract: This research aims to analyze the impact of Business Capability and Digital Marketing on Business Sustainability in 100 SMEs in Sambas Regency (Songket Weaving) and Bengkayang Regency (Bamboo Crafts), border regions of Indonesia. The analysis results indicate that Digital Marketing has a higher positive impact (0.493) compared to Business Capability (0.348) on Business Sustainability. This suggests that Digital Marketing strategies have a more significant contribution to enhancing the sustainability of SMEs in the border region. Furthermore, in the context of SEM construction, all items related to Business Capability (X1), Digital Marketing (X2), and Business Sustainability (Y) have high outer loadings, with most values above 0.9, verifying the reliability and validity of the measurements. Model-fit indicates that the estimated model fits the observational data very well, with an R-Square value reaching 66.6%. These findings provide a strong understanding of the factors influencing SME sustainability in this border region, emphasizing the importance of implementing Digital Marketing strategies to support SME growth in the future..